Tenaga Kerja Bongkar Muat Pasca Pemberlakuan Asas Cabotage di Indonesia - Gultom, Elfrida Ratnawati; Nurbaiti, Siti (Universitas Semarang, 2022)
The purpose of this writing is to discuss TKBM work opportunities in ports after the implementation of the Cabotage principle in Indonesia, because of its important role in the sea transportation process and is needed by the port community as a tool for loading and unloading goods on ships, and/or offshore activities in Indonesian sea waters. as well as other activities. The process of loading and unloading of goods on board is carried out by the Loading and Cabotage Workforce is a principle that enforces a rule that foreign ships are prohibited from loading and unloading goods in Indonesian waters, the aim is to empower national shipping. The performance of TKBM after the application of the Cabotage principle is discussed in this study which uses a conceptual framework supported by secondary data as library material and is analyzed descriptively. The results of the study show that after the implementation of the cabotage principle, the number of Indonesian ships continues to increase until 2022 is recorded at 33,000, because this principle prohibits foreign ships from transporting goods and passengers in Indonesian waters, except for ships with red and white flags only, and with the enactment of the principle In fact, the performance of TKBM in Indonesian Ports is getting higher. Tujuan penulisan ini membahas tentang peluang kerja tenaga kerja bongkar muat (TKBM) di pelabuhan setelah diberlakukannya asas Cabotage di Indonesia, karena perannya yang penting dalam proses pengangkutan laut dan dibutuhkan oleh masyarakat Pelabuhan sebagai alat pembantu kegiatan bongkar muat barang di kapal, dan/atau kegiatan lepas pantai di perairan laut Indonesia serta kegiatan lain. Asas Proses bongkar dan muat barang di atas kapal dilakukan oleh tenaga kerja bongkar muat dan Cabotage merupakan asas yang memberlakukan suatu aturan bahwa kapal asing dilarang untuk bongkar muat barang di perairan Indonesia, tujuannya untuk memberdayakan pelayaran nasional. Bagaimana kinerja TKBM pasca diberlakukannya asas Cabotage adalah bahasan dalam penelitian ini yang menggunakan kerangka konsep didukung data sekunder sebagai bahan pustaka dan dianalisis secara deskriptif. Hasil penelitian menunjukkan, bahwa setelah diberlakukannya asas Cabotage, jumlah kapal Indonesia terus bertambah hingga tahun 2022 tercatat sebanyak 33.000 an, dikarenakan asas ini melarang kapal asing untuk mengangkut barang dan penumpang di perairan Indonesia, kecuali kapal yang berbendera merah putih saja, dan dengan diberlakukannya asas ini, justru kinerja TKBM di Pelabuhan Indonesia semakin tinggi.